A Retrospective Assessment of the Use of Naltrexone Implants for the Treatment of Problematic Amphetamine Use. (7th February 2013) - Kelty, Erin; Thomson, Karen; Carlstein, Sarah; Sinclair, Rebecca; Hulse, Gary
<x xml:space="preserve">Abstract</x> Background At present there is no registered effective pharmacotherapy for the treatment of problematic amphetamine use. Objectives This study aims to examine self‐reported abstinence from amphetamines following treatment with a sustained release naltrexone preparation in patients with self and clinically identified problems with amphetamine use and the relationship between naltrexone blood levels and abstinence from amphetamines. Methods Forty‐four patients with problematic amphetamine use, who were treated with a naltrexone implant, completed an interview evaluating self‐reported reduction in amphetamine use following treatment. Additional data were collected from the patients' clinical treatment files. Results Of the 44 subjects, 29 (65.9%) interviewed reported that following treatment they ceased using and maintained abstinence from amphetamines for at least 1 month. Of these patients, 14 (48.3%) were reportedly still abstinent at 6 months. Rates of abstinence were found to be 2.27 times higher (95% CI 1.38–3.74) in patients when blood naltrexone levels were above 2 ng/ml, with rates as high as 100% and 90.9% for ≥5 and ≥2 ng/ml, respectively, compared with 42.9% for 1–2 ng/ml and 38.9% low less than 1 ng/ml. Conclusions Although this study has several limitations, the findings provide preliminary data in support of the use of implant naltrexone for the treatment of problematic amphetamine use and suggest that naltrexone levels above 2 ng/ml should be targeted for use in patients. Scientific Significance Data supports the use of implant naltrexone, as a treatment for problematic amphetamine use, for which there is currently no registered pharmacotherapy. However, further research is required. (Am J Addict 2013;22:1‐6)